THE FISHES OF SEAGRASS COMMUNITY ON THE WEST SIDE OF BURUNG ISLAND (PARI ISLANDS, SERIBU ISLANDS) AND THEIR VARIATIONS IN ABUNDANCE - Hutomo, Malikusworo; Martosewojo, Sularto (Marine Research in Indonesia, 1977)
Monthly collections of fishes in a seagrass community on the west of Burung Island, Pari Islands, were made from May 1975 to February 1976. Seventy-eight species of fishes were collected. Number of specimens, size range, and modal size are given for each month for each species. Number of species and specimens were found highest in July. Relative and total abundances of the more numerous species are summarized. Apogon margaritophorus was the predominant species in the fish community of the area. Notes on the spawning of Siganus canaliculatus are presented, since this species attracts the attention of many mariculturists. The separation of these fishes into four groups is also discussed.